2015
DOI: 10.1159/000375152
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Patent Foramen Ovale in Ischaemic Stroke in Italy: Results of SISIFO Study

Abstract: Background: Although several authors have studied the association between patent foramen ovale (PFO) and ischaemic stroke, the matter is still controversial; few have suggested an association between cryptogenetic stroke and PFO, while others have denied this association. The aim of this study was to evaluate PFO prevalence in the whole ischaemic stroke population, independently from age and stroke subtypes and to identify the characteristics associated with the presence of PFO. Methods: SISIFO study was a mul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
17
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 38 publications
5
17
0
1
Order By: Relevance
“…Although PFO screening in SIFAP study was not mandatory, we got data from nearly 80% of all patients. Finally, the rates of PFO in our cryptogenic stroke cohort are in accordance with those of several other studies, 21,35,36 making underreporting because of a lack of information or overestimation by PFO screening unblinded to the clinical situation 37 unlikely. In agreement with other studies, 22 even in SIFAP1 study, the PFO prevalence was generally higher in younger patients.…”
Section: January 2017supporting
confidence: 91%
“…Although PFO screening in SIFAP study was not mandatory, we got data from nearly 80% of all patients. Finally, the rates of PFO in our cryptogenic stroke cohort are in accordance with those of several other studies, 21,35,36 making underreporting because of a lack of information or overestimation by PFO screening unblinded to the clinical situation 37 unlikely. In agreement with other studies, 22 even in SIFAP1 study, the PFO prevalence was generally higher in younger patients.…”
Section: January 2017supporting
confidence: 91%
“…As described previously,8, 22 contrast agent was generated by agitating a mixture of 9 mL of isotonic saline solution and 1 mL of air between two 10 mL syringes connected by a three‐way stopcock. A drop of the patient's blood was allowed to mix with the contrast agent, which can slightly increase the detection sensitivity.…”
Section: Methodsmentioning
confidence: 99%
“…Epidemiological studies demonstrated that the prevalence of patent foramen ovale (PFO) in CS patients (40–56%) is much higher than that in normal healthy population (4–18%), suggesting a potential association between PFO and CS 4, 5, 6, 7. PFO may act as the pathway of thrombi from the venous circulation to cerebral circulation2 and could induce transient arrhythmia, both of which are recognized as potential underlying mechanisms for PFO‐induced CS 8. However, some researchers considered PFO as an anatomic variant,9 which could be just an incidental event for CS, rather than a cause 8, 10.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, it would be of great interest to reasonably integrate the role of PFO alone and PFO with ASA into concurring etiologies for ischemic stroke. A number of studies tried to address this question, unfortunately with major shortcomings, as they had either smaller study populations [2], or right-left-shunt analysis was done by neurological doppler/duplexsonography with a bubble test [11], whereby it is impossible to distinguish between shunts on cardiac or pulmonary level.…”
Section: Introductionmentioning
confidence: 99%